1996
DOI: 10.1007/s001250050629
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Blood Pressure Control in NIDDM (ABCD) Trial

Abstract: There is considerable epidemiologic evidence suggesting that hypertension plays a significant role in the development and progression of diabetic nephropathy [1], retinopathy [2,3], cardiovascular disease [4][5][6][7], and neuropathy [8] in patients with non-insulindependent diabetes mellitus (NIDDM). Furthermore, several studies have demonstrated a significant increase in mortality in diabetic patients with hypertension [9,10]. Although the epidemiological evidence demonstrating the strong association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…In recent years, A1c levels have improved with the increased availability of more effective pharmacologic agents including new insulins, metformin, and thiazolidinediones, with marked A1c improvement noted in some care settings (13)(14)(15)(16). Similarly, more effective pharmacologic strategies have been developed and disseminated for the primary and secondary prevention of cardiovascular disease, and studies have shown that the use of statins (17,18), fibrates (19), ACE inhibitors (20), and more aggressive control of hypertension (21,22) reduce cardiovascular morbidity and mortality in those with diabetes. Data show that A1c levels tend to rise with duration of diabetes (23), and the prevalence of depressive symptoms appears to be increased among those with diabetes (24) due to several factors (25)(26)(27).…”
mentioning
confidence: 99%
“…In recent years, A1c levels have improved with the increased availability of more effective pharmacologic agents including new insulins, metformin, and thiazolidinediones, with marked A1c improvement noted in some care settings (13)(14)(15)(16). Similarly, more effective pharmacologic strategies have been developed and disseminated for the primary and secondary prevention of cardiovascular disease, and studies have shown that the use of statins (17,18), fibrates (19), ACE inhibitors (20), and more aggressive control of hypertension (21,22) reduce cardiovascular morbidity and mortality in those with diabetes. Data show that A1c levels tend to rise with duration of diabetes (23), and the prevalence of depressive symptoms appears to be increased among those with diabetes (24) due to several factors (25)(26)(27).…”
mentioning
confidence: 99%
“…here is extensive clinical evidence linking hypertension with microand macrovascular complications of diabetes, including randomized controlled trials and a meta-analysis (1)(2)(3)(4)(5)(6). Until 2000, the target blood pressure for individuals with diabetes was the same as that for individuals without diabetes (Ͻ140/90 mmHg).…”
mentioning
confidence: 99%
“…The Appropriate Blood Pressure Control in Diabetes (ABCD) trial has provided valuable evidence for the excellent efficacy of nisoldipine, a calcium channel blocker, as a first-line antihypertensive agent in preventing or delaying the progression of diabetic nephropathy, retinopathy, neuropathy and cardiovascular disease with Type II (non-insulin-dependent) diabetes mellitus [8]. This clinical trial stresses the importance of intensive blood pressure control for reducing the risk of cardiovascular events in hypertensive patients with Type II diabetes.…”
mentioning
confidence: 99%
“…Indeed, calcium channel blockers such as amlodipine have been shown to improve cardiac remodelling in spontaneously hypertensive rats [26], myocardial infarcted rats [27] and idiopathic dilated cardiomyopathic hamsters [28]. In the light of the clinical studies showing the efficacy of calcium channel blocker therapy in preventing cardiovascular disease in patients with diabetes [8,9], the favourable actions of treatment with calcium channel blockers on cardiovascular functions in diabetes might be partly based on their beneficial effects on the remodelling process associated with growth factors causing cardiac angiogenesis and fibrosis. However, it is not clear what role is played by angiogenic growth factors in cardiac remodelling during diabetes.…”
mentioning
confidence: 99%